APPLICATION OF ENERGY-SAVING AND GREEN ARCHITECTURE TECHNOLOGIES IN THE ARCHITECTURAL AND URBAN PLANNING DEVELOPMENT OF CITIES IN THE ARAL SEA REGION (KIUT Publication, 2025)
This article highlights the issue of introducing energy-saving and green architecture technologies into the urban planning process in areas with ecologically sensitive and climatically challenging conditions, such as the Aral Sea region. Based on scientific sources, energy-saving, green infrastructure, and climate-appropriate architectural strategies are analyzed, and practical recommendations for the Aral Sea region are provided.